PENERAPAN PEMBELAJARAN BLENDED LEARNING DAPAT MENINGKATKAN HASIL BELAJAR SISWA KELAS VIIIG SMP NEGERI 1 TABANAN DI ERA NEW NORMAL PANDEMI COVID 19 - Widyantari, Gusti Ayu Aris (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
This research was a classroom action research (CAR) which aimed to improve the students’ learning outcomes at SMP Negeri 1 Tabanan, especially in VIIIG class in the academic year 2021/2022, namely by applying blended learning. This classroom action research was carried out in 2 cycles, namely cycle I and cycle II, which was carried out in VIIIG class of SMP Negeri 1 Tabanan in the academic year 2021/2022 with a total of 39 students. The learning outcomes data was obtained from the learning outcomes tests. Then the data collected was then analyzed by descriptive method. The results showed that the application of the blended learning could improve the students’ learning outcomes in VIII G class of SMP Negeri 1 Tabanan in the new normal era of the Covid 19 pandemic from the average of 72.87 and 61.54% completeness to the average of 80.18 and 87,18% completeness. From the results of this study it could be concluded that the blended learning could improve the students’ learning outcomes because this learning model was very suitable to be applied in the new normal era of the Covid 19 pandemic. Teachers could be more innovative in carrying out the learning by conducting the classroom action research.